VisJockey: Enriching Data Stories through Orchestrated Interactive Visualization - Kwon, Bum Chul; Stoffel, Florian; Jäckle, Dominik; Lee, Bongshin; Keim, Daniel (2014)
Visualization has recently begun to extend its role into a communication medium for presentation and storytelling. With the advancement in web-based visualization technology (e.g., D3), we increasingly encounter an integration of interactive visualizations into data stories in news media, blog posts, etc. However, these stories usually do not provide enough guidance on how to interpret and manipulate the accompanied visualizations. Therefore, readers are often on their own in finding the right state and area of visualization authors intended to show to support their arguments. We introduce VisJockey, a technique that enables readers to easily access authors’ intended view through orchestrated visualization. To offload readers’ burden in making connections between the text and the visualization, VisJockey augments the visualization through highlight, annotation, and animation. We describe the main concept of VisJockey and present three example stories.
Computation+Journalism 2014